First Identification of Rare Exonic and Deep Intronic Splice-Altering Variants in Patients With Beta-Sarcoglycanopathy - Xie, Zhiying; Sun, Chengyue; Liu, Chang; Chu, Xujun; Gang, Qiang; Yu, Meng; Zheng, Yiming; Meng, Lingchao; Li, Fan; Xia, Dongliang; Wang, Li; Li, Ying; et al. (Frontiers in Pediatrics, 2022)
Background: The precise genetic diagnosis of a sarcoglycanopathy or dystrophinopathy is sometimes extremely challenging, as pathogenic non-coding variants and/or complex structural variants do exist in DMD or sarcoglycan genes. This study aimed to determine the genetic diagnosis of three patients from two unrelated families with a suspected sarcoglycanopathy or dystrophinopathy based on their clinical, radiological, and pathological features, for whom routine genomic detection approaches failed to yield a definite genetic diagnosis. Methods: Muscle-derived reverse transcription-polymerase chain reaction analysis and/or TA cloning of DMD, SGCA, SGCB, SGCD, and SGCG mRNA were performed to identify aberrant transcripts. Genomic Sanger sequencing around the aberrant transcripts was performed to detect possible splice-altering variants. Bioinformatic and segregation studies of the detected genomic variants were performed in both families. Results: In patients F1-Ⅱ1 and F1-Ⅱ2, we identified two novel pathogenic compound heterozygous variants in SGCB. One is a deep intronic splice-altering variant, c.243+1558C>T in intron 2 causing the activation of an 87-base pair (bp) pseudoexon, and the other one is a non-canonical splicing site variant, c.243+6T>A leading to the partial intron inclusion of 10-bp sequence. A novel deep intronic splice-altering variant, c.243+1576C>G causing a 106-bp pseudoexon activation, and a nonsense variant in SGCB were identified in compound heterozygous state in patient F2-Ⅱ1. Unexpectedly, the predicted nonsense variant, c.334C>T in exon 3, created a new donor splice site in exon 3 that was stronger than the natural one, resulting in a 97-bp deletion of exon 3 (r.333_429del). Conclusion: This is the first identification of rare exonic and deep intronic splice-altering variants in the SGCB gene.